FACTORS AFFECTING THE CAPITAL STRUCTURE OF ISLAMIC MICROFINANCE INSTITUTIONS : INSIGHTS FROM RURAL BANKS IN INDONESIA - INDANAZULFA QURROTA A’YUN; MUHAMMAD SAFAR NASIR (LP2MTBM MAKARIOZ, 2021)
Optimal capital structure is a balance between the use of their own capital with long-term loans; intention is how much oftheir own with the use of long-term loan that will be used so that it can be optimal. Capital structure or funding decisions willgreatly affect the performance of the company. The purpose of this study is to examine the determinants of capital structureof Islamic Sharia Rural Bank in Indonesia, using panel financial data of 157 rural banks drawn from 2010 to 2019 on aquartely basis. A panel regression techique was applied, using fixed effects to estimate the relationship between capitalstructure and bank-specific variables such as growth, profitability, bank size and asset structure. The results indicates thatasset structure is statistically significant in determining the capital structure of islamic rural banks in Indonesia, comformingto the pecking order theory, trade theory, costs bankruptcy theory as well as the agency theory. However, growth is notsignificant in affecting the bank capital structure. Correspondingly, the results shows that profitability and bank size havenegative and significant effect on bank capital structure. Results of this study provide support to bank managers tounderstand the effect of bank-specific variables on capital structure.